Sex and the city : the complete fourth season - Bicks, Jenny; King, Michael Patrick, 1954-; Star, Darren, 1961-; Green, Michael, MD.; Algrant, Dan, 1959-; Parker, Sarah Jessica; Cattrall, Kim.; Davis, Kristin, 1966-; Nixon, Cynthia; Noth, Chris, 1954-; Corbett, John, 1961-; Garson, Willie, 1964-; et al. (New York, NY : HBO Video, 2003)
Will acclaimed sex columnist Carrie get back together with Mr. Big or will she end up with Aidan? Will Charlotte and Trey be able to live happily ever after? Will Samantha and Miranda ever commit to anything that resembles a lasting relationship? Find out in the eighteen shows of season four
Information from pre-release promotional materials; release date: May 20, 2003
Originally released as a television series - fourth season from 2001-2002
Based on the the character created by Darren Star and the novel by Candace Bushnell
Special features: 3 audio commentaries by executive producer Michael Patrick King; episodic previews; cast and filmmaker biographies
Director of photography, Stuart Dryburgh ... [et al.] ; editor, Kate Stanford ; original music, Douglas J. Cuomo ; costume designer, Ellen Lutter ; production designer, Mark Friedberg
Sarah Jessica Parker, Kim Cattrall, Kristin Davis, Cynthia Nixon, Chris Noth, John Corbett, Willie Garson, David Eigenberg
Keywords: Journalists -- Drama; Women -- Sexual behavior -- Drama; Television comedies; DVD-Video discs; Video recordings; Drama